Localizing the position of the Segond fracture bed under CT measurements to determine the functional tibial insertion of an anterolateral ligament - Guo, Ziteng; Wang, Xuyang; Liu, Guoshuai; Lu, Yang; Bai, Yuxi; Lv, Jian; Liu, Fei (Frontiers in Surgery, 2023)
Background: Many studies have confirmed the existence of ligament structures in the anterolateral region of the knee that maintain rotational stability of the knee joint, namely the anterolateral ligament (ALL). At present, there is little research on the lateral ALL tibia insertion point, and most clinicians use the midpoint Gerdy's tubercle and fibular head as insertion point. However, the reconstruction effect is not ideal. Objective: To measure the position of Segond fracture bed on CT images to determine ALL position of the tibia. Method: The CT AM Volume Share 2 system was used to manually measure the position of bone fragments in 23 Segond fracture patients. CT sagittal slice measures the vertical distance from the center of Segond fracture bed to the segment of the Gerdy-fibular line segment (G-F line segment), which is the line connecting the highest point of the segment to the outermost point of the fibula. The length of vertical point at the center of Segond fracture bed of the G-F line to the highest point of the Gerdy tubercle was measured. All measurements were performed using the same measurement standard, expressed as a percentage of the length of the G-F line. The measured results were statistically analyzed using SPSS 25.0 descriptive statistical research methods. Results: The average length of the G-F segment measured on CT images was 39.6 ± 2.0mm, the average vertical length from the center of the Segond fracture bed to the G-F segment is 13.1 ± 1.1mm, accounting for 33.2% ± 2.1% of the length of G-F segment. The length from fracture bed vertical point on the G-F line segment to the highest point of the Gerdy tubercle is 14.7 ± 1.3mm, accounting for 37.1% ± 2.9% of the length of G-F segment. Conclusion: Through the study of CT measurement of Segond fracture location, we obtained the location of functional tibial insertion of ALL, which is different from the anatomical insertion of ALL, and is more inclined to Gerdy tubercle and above, which has reference value for the treatment of recovering the function of anterolateral ligament after reconstruction